2019
DOI: 10.1002/eat.23181
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective case series of electroconvulsive therapy in the management of comorbid depression and anorexia nervosa

Abstract: Objective Major depressive disorder (MDD) is common in anorexia nervosa (AN), associated with worse outcome and greater suicide risk. Electroconvulsive therapy (ECT) is highly effective in the treatment of MDD refractory to antidepressive treatment. We describe a case series of female adolescents with AN receiving ECT for MDD resistant to treatment and/or with severe suicide risk. Method We retrospectively analyzed the files of all 30 adolescent females hospitalized in our department because of AN between 1998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…There was one case series that included adolescent patients. In a case series of 30 female adolescent patients with anorexia nervosa who were hospitalized and treated with ECT due to severe suicidal risk (severe suicidal ideation or suicide attempt), only one patient attempted suicide during ECT treatment, and no patients completed suicide following ECT treatment (Shilton et al, 2020). Depression severity also significantly decreased after ECT treatment (vs. before ECT).…”
Section: Case-control Studiesmentioning
confidence: 97%
“…There was one case series that included adolescent patients. In a case series of 30 female adolescent patients with anorexia nervosa who were hospitalized and treated with ECT due to severe suicidal risk (severe suicidal ideation or suicide attempt), only one patient attempted suicide during ECT treatment, and no patients completed suicide following ECT treatment (Shilton et al, 2020). Depression severity also significantly decreased after ECT treatment (vs. before ECT).…”
Section: Case-control Studiesmentioning
confidence: 97%
“…Indeed, due to the high suicide rate in patients with EDs, intensive treatments, like ECT, are often proposed. The recent and largest case series on patients with AN treated by ECT concerned 30 adolescents with comorbid depression [62]. All were severely depressed and suicidal upon admission and resistant to antidepressants.…”
Section: Anorexia Nervosamentioning
confidence: 99%
“…In their study targeting two areas in the same trial for the first time, the targets were chosen based on two of the major psychiatric comorbidities associated with AN: SCC for affective disorder (n = 4) and NAcc for anxiety disorder (n = 4) [102]. Indeed, most studies reported positive effects on depressive symptoms with rTMS [26], tDCS [56], ECT [62], and DBS [93]. Future studies in EDs might benefit from this knowledge in brain target selection (Figure 1), in studies design (add-on with another modalities of treatment, inclusion and exclusion criteria, etc.…”
Section: Current Evidence and Issuesmentioning
confidence: 99%
“…A more recent review examined the data of adolescent case files (between 1998 and 2017) from an Israel medical center [55]. Of 667 patients hospitalized over the period due to severe AN, 4.5% of the patients (n = 30) received ECT.…”
Section: Electroconvulsive Therapymentioning
confidence: 99%